Studies on the Metabolites of a Fungal Endophyte Penicillium sp. HS-5 from Huperzia serrata - Ying, You-Min; Shan, Wei-Guang; Liu, Wen-Hong; Zhan, Zha-Jun (Asian Journal of Chemistry, 2012)
Nine compounds 1-9 were isolated from the broth of the strain Penicillium sp. HS-5, a fungal endophyte living in Huperzia serrata. Structures of the isolated compounds were identified as Sumiki's acid (1), acetyl Sumiki's acid (2), 2-furoic acid (3), kojic acid (4), 4-hydroxybenzonic acid (5), adenosine (6), adenine (7), thymine (8) and ergosterol (9) by NMR and MS analysis as well as by comparison of their physio-chemical and spectroscopic data with literatures. Compounds 1-4 were isolated for the first time from a fungal endophyte of Huperzia serrata and subjected to an antibacterial assay against S. aureus ATCC 29213, a MRSA strain.